IMPLEMENTASI MANAJEMEN SANTRI DI DAYAH TERPADU AL-MUSLIMUN - Asra Amalia; Asnawi; Agus Salim Salabi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of santri at Dayah Terpadu Al-Muslimun, which covers four main pillars: admission and selection systems, santri guidance and development services, monitoring and evaluation of development, and alumni management and contribution networks. The approach used is qualitative with a case study research type, through interviews, observation, and documentation of caregivers, musyrif/musyrifah, santri, and alumni. The results of the study show that the student admission system is digital-based and applies the principles of transparency and accountability; guidance services are implemented holistically, covering spiritual, academic, character, and digital literacy aspects; monitoring and evaluation are carried out collaboratively but still require standard instruments; while the alumni network plays an active role in supporting the strengthening of the institution's reputation and sustainability. The research conclusion confirms that santri management at Dayah Terpadu Al-Muslimun has been effective andintegrated, combining Islamic values with modern quality-based management principles.These results are expected to serve as a reference model for developing santri management systems in other Islamic educational institutions.